Research on Cryopreservation Conditions of Attached HepG2 Cells on PDMS-glass Microfluidic Chip - Zhou Xinli; Peng Tian; Wang Biao (Zhileng xuebao)
Efficient cryopreservation of cell samples on microfluidic chips can significantly shorten the cycle of cell experiments on chips, reduce the cost of experiments, which will contribute to the wide application of cell experiments on chips. In this paper, the cryopreservation of the attached HepG2 cells on PDMS-glass microfluidic chip was examined. Furthermore, the cooling rate, cryoprotectant, storage time and temperature, and the cryopreservation protocol of the attached HepG2 cells on the chip was determined. The results indicated that a cooling rate of 0.36–35.12 ℃/min can be realized in the chip microchannel by using different cooling environments and cooling mediums. There is an optimal cooling rate of 0.5–1.5 ℃/min in cryopreservation of HepG2 cells. Furthermore, at -20 ℃ or 40 cm above the surface of liquid nitrogen cooling environment combined with -80℃cooling environment can significantly increase the viability of7d frozen HepG2 cells on chip. Additionally, DMSO with a volume concentration of 20% combined with 0.1 mol/L trehalose can significantly enhance the activity of cryopreserved HepG2 cells on chip. After optimization of the aforementioned cryopreservation conditions, the attached HepG2 cells on chip were successfully stored for 7d with a viability of more than 90%.